Association between motivation and decision-making in under-18 male volleyball players - de Oliveira Castro, Henrique; da Silva Aguiar, Samuel; Clemente, Filipe Manuel; Lima, Ricardo Franco; de Oliveira, Vivian; Ribas, Schelyne; Pedrosa, Gustavo Ferreira; Laporta, Lorenzo; de Conti Teixeira Costa, Gustavo (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Motivation and decision-making are important variables of sports performance. In this perspective, identifying whether motivation is associated with decisions made by athletes is essential to provide environments that facilitate the achievement of better performances. Aim of Study. The objective was (a) to analyze the decision-making and levels of motivation among male under-18 volleyball athletes with different levels of experience; and (b) associating motivation and decision-making in different game situations (attack from central and court extremities, setting, and blocking). Material and Methods. In the study, 92 high-performance male volleyball athletes from the under-18 category were divided into two groups: more experienced group (G1) and less experienced group (G2). The motivation level was analyzed by the Sport Motivation Scale-II, and the Declarative Tactical Knowledge Test in Volleyball was used to analyze the decision-making. Results. The results revealed a positive, but weak and significant correlation between the attack from the extremity and integrated motivation, and among intrinsic and introjected and external motivation. There was also a positive, moderate, and significant correlation between introjected and external motivation. Besides, G1 showed less intrinsic, introjected, and external motivation when compared to G2. Regarding decision-making, G1 showed higher values for central attack and lower values for setting and blocking, when compared to G2. Conclusions. It is concluded that better decisions of under-18 volleyball athletes in situations of attack from extremity are associated with a higher occurrence of integrated (extrinsic) motivation and more experienced volleyball athletes have a prevalence of intrinsic and extrinsic motivation when compared to less experienced athletes.
Keywords: cognition; sport psychology; sports training; young athletes; team sports